Related Knowledge and Support Family Mother Pregnant Women Attitudes about Prenatal Care (ANC) - Aritonang, Dor Valda A; Adiwijaya, Saputra; Wulandari, Anggun; Anita D, Nyoman (Budapest International Research and Critics University, 2019)
Antenatal care is a service provided to mothers in the process of pregnancy and to provide assurance that the mother and fetus are safe in pregnancy and childbirth. In the 2013 Riskesdas, the coverage of antenatal care for pregnant women increased.However, the coverage of K1 and K4 in East Java still has not reached 100%. The purpose of this study was to determine the mother's knowledge and family support for the attitudes of pregnant women regarding ANC in the work area of Gunung Anyar Public Health Center, Surabaya City. This study used a cross sectional study design. The population was 1089 pregnant women and samples were taken using the Slovin formula of 75 people. The statistical test used is Chi Square test with a confidence level of 95%. The results show that pregnant women who have poor knowledge of 46 people (61.3%), pregnant women who get less family support are 28 people (37.3%), and pregnant women who have a negative attitude about ANC of 42 people ( 56.0%). The p-value between mother's knowledge and family support with the mother's attitude about ANC is 0.012 and 0.744. The conclusion is that there is no relationship between maternal knowledge and family support with the mother's attitude about ANC.